1999
DOI: 10.1007/bf03395305
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Acceptance Versus Control Rationales on Pain Tolerance

Abstract: Acceptance approaches , which have been receiving increased attention within behavior therapy, seek to undermine the linkage between private events and overt behavior, rather than attempting to control the form or frequency of private events per se. Research comparing control versus acceptance strategies is limited. The present study examined the behavioral and subjective impact of a control-based versus acceptance rationale, using a cold pressor task. Subjects in the acceptance group demonstrated greater tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
225
2
11

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(254 citation statements)
references
References 15 publications
16
225
2
11
Order By: Relevance
“…RFT has proven itself successful so far in modeling the nature, acquisition, and impact of higher cognition at the behavioral, emotional, and neurobiological level. For example, RFT researchers have successfully modeled analogy and metaphor (Stewart, Barnes-Holmes, & Roche, 2004), trained perspective taking (xx), ad RFT tasks can successfully model the natural language tasks studied in basic cognitive science, such as semantic priming (Bissett & Hayes, 1999;Barnes-Holmes. Xxx 2003) or xxx.…”
Section: Act Theoretical Rootsmentioning
confidence: 99%
“…RFT has proven itself successful so far in modeling the nature, acquisition, and impact of higher cognition at the behavioral, emotional, and neurobiological level. For example, RFT researchers have successfully modeled analogy and metaphor (Stewart, Barnes-Holmes, & Roche, 2004), trained perspective taking (xx), ad RFT tasks can successfully model the natural language tasks studied in basic cognitive science, such as semantic priming (Bissett & Hayes, 1999;Barnes-Holmes. Xxx 2003) or xxx.…”
Section: Act Theoretical Rootsmentioning
confidence: 99%
“…27,28,29,30,31,42,47,76 The PF model as a whole is currently not well known within the field of chronic pain. Some of its six constituent processes of PF, however, are gaining prominence, especially acceptance, 4,10,11,18,26,56,58,69,84,87,97 and values-based action. 55,56,59,67,84 Even the least well recognized processes of PF now have some empirical support, including present-focused awareness, 51 cognitive defusion and self-as-observer, 53 and committed action.…”
Section: Current Psychological Models Of Chronic Pain Under a Microscopementioning
confidence: 99%
“…For a number of years, analogue studies have demonstrated acceptance of difficult or distressing experiences in the laboratory (e.g., Hayes et al, 1999;Zettle, 2005). Citing the theoretical rationale that values provide the context in which acceptance is possible (one does not typically accept discomfort simply for its own merit), assessing the additive impact of personal values to an acceptance intervention for a distressing task is the logical next step.…”
Section: Empirical Support For the Process Of Values In Actmentioning
confidence: 99%